2011
DOI: 10.1371/journal.pmed.1001120
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Tuberculosis with the Xpert MTB/RIF Assay in High Burden Countries: A Cost-Effectiveness Analysis

Abstract: A cost-effectiveness study by Frank Cobelens and colleagues reveals that Xpert MTB/RIF is a cost-effective method of tuberculosis diagnosis that is suitable for use in low- and middle-income settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
294
8
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 285 publications
(326 citation statements)
references
References 24 publications
15
294
8
9
Order By: Relevance
“…Vassall et al, reported the cost for the Xpert test (including all costs, such as the cartridge, equipment, salaries) ranges from US$22.63 in India to US$27.55 in Uganda [21]. Due to IPAQT (www.ipaqt.org; a coalition of private labs in India, supported by industry and nonprofit groups), the maximum price labs can charge patients for Xpert MTB/RIF is now Rs.…”
Section: Discussionmentioning
confidence: 99%
“…Vassall et al, reported the cost for the Xpert test (including all costs, such as the cartridge, equipment, salaries) ranges from US$22.63 in India to US$27.55 in Uganda [21]. Due to IPAQT (www.ipaqt.org; a coalition of private labs in India, supported by industry and nonprofit groups), the maximum price labs can charge patients for Xpert MTB/RIF is now Rs.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos sugerem que o Xpert MTB/RIF é custo-efetivo em diferentes cenários 11,12,13,14,15 . Também no Brasil, um país de média renda, o teste para uma amostra de escarro se mostrou mais custo-efetivo 15 do que a baciloscopia de duas amostras diagnós-ticas na perspectiva do SUS.…”
Section: Introductionunclassified
“…Smear microscopy, HIV-negative 0.654 [5,8,13] Smear microscopy, HIV-positive 0.404 [5,8,13] Xpert MTB/RIF, smear-positive TB cases 0.983 [5,8] Xpert MTB/RIF, smear-negative, HIV-negative cases 0.793 [5,8] Xpert MTB/RIF, smear-negative, HIV-positive cases 0.718 [5,8] Xpert MTB/RIF rifampin testing 0.983 [5,8] Clinical diagnosis of TB 0.444 [5,8] Specificity Smear microscopy 0.982 [5,8,13] Xpert MTB/RIF 0.990 [5,8] Xpert MTB/RIF rifampin testing 0.983 [5,8] Clinical diagnosis of TB 0.869 [5,8] Return for results, probability (range)…”
Section: Sensitivitymentioning
confidence: 99%
“…The feasibility and cost-effectiveness of the Xpert have been well studied and support the implementation of the device in resource-limited settings [4][5][6][7][8]. When allocating new diagnostics, it has been recommended that public health decision-makers utilize not only data from such technical studies and registration trials, but also examine the existing epidemiology, health care infrastructure and clinical practice to optimize implementation and scale up [9].…”
Section: Introductionmentioning
confidence: 99%